2019
DOI: 10.3390/s19214607
|View full text |Cite
|
Sign up to set email alerts
|

Paper-Based ZnS:Cu Alternating Current Electroluminescent Devices for Current Humidity Sensors with High–Linearity and Flexibility

Abstract: Humidity sensors are indispensable for various electronic systems and instrumentations. To develop a new humidity sensing mechanism is the key for the next generation of sensor technology. In this work, a novel flexible paper-based current humidity sensor is proposed. The developed alternating current electroluminescent devices (ACEL) consist of the electroless plating Ni on filter paper and silver nanowires (AgNWs) as the bottom and upper electrodes, and ZnS:Cu as the phosphor layer, respectively. The propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Because of this advantage, the powder EL devices, which can be fabricated by 3D printing [ 1 , 2 ], exhibit good mechanical durability, such as bending durability [ 3 ], flexibility [ 4 ], and stretchability [ 5 , 6 ]. They can also be used as sensors for ammonia [ 7 ], carbon dioxide [ 8 ], humidity [ 9 ], and temperature [ 10 ]. Unique functionalities, such as the self-recovery of their structure [ 11 , 12 , 13 ] and the generation of sound [ 14 , 15 , 16 ], have also been developed through the powder EL system.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this advantage, the powder EL devices, which can be fabricated by 3D printing [ 1 , 2 ], exhibit good mechanical durability, such as bending durability [ 3 ], flexibility [ 4 ], and stretchability [ 5 , 6 ]. They can also be used as sensors for ammonia [ 7 ], carbon dioxide [ 8 ], humidity [ 9 ], and temperature [ 10 ]. Unique functionalities, such as the self-recovery of their structure [ 11 , 12 , 13 ] and the generation of sound [ 14 , 15 , 16 ], have also been developed through the powder EL system.…”
Section: Introductionmentioning
confidence: 99%
“…Humidity sensor. Reproduced with permission from ref . Copyright 2019 Molecular Diversity Preservation International.…”
Section: Conclusion Challenges and Outlookmentioning
confidence: 99%
“…That means the ACEL device can respond well to temperature changes through EL intensity. He et al 135 reported a filter paperbased current humidity ACEL sensor. Due to the synergetic function of filter paper and ZnS:Cu, the sensor exhibits excellent linearity (R 2 = 0.99965) within humidity range from 20% to 90%.…”
Section: Multifunctional Displays and Sensing Platformsmentioning
confidence: 99%
“…Thus, a large number of researchers are committed to developing high-performance sensors (e.g., accurate results, high sensitivity, excellent reliability, rapid response/recovery time, good repeatability, low cost, etc. ). So far, depending on different working principles, humidity sensors are classified into resistive humidity sensors, capacitive sensors, , optical fiber humidity sensors, , and bulk acoustic wave (BAW) humidity sensors. , Among them, quartz crystal microbalance (QCM), a typical BAW device, is becoming a research hotspot with advantages of high sensitivity, low cost, easy operation, and digital output. …”
Section: Introductionmentioning
confidence: 99%